Effect of Spectral Quality of Monochromatic LED Lights on the Growth of Artichoke Seedlings - Rabara, Roel C. (Front Plant Sci, 2017)
Indoor farming is becoming a popular alternative approach in food production to meet the demand of a growing world population. Under this production system, artificial light provides the main source of illumination in sustaining plant growth and development. The use of light-emitting diodes (LEDs) is a popular source of artificial light for indoor farms due to its narrow light spectra, modular design and energy efficiency. This study purposely assessed the effect of monochromatic LED light quality on the growth of three varieties of artichoke seedlings compared to greenhouse condition. Spectral quality assessment showed that photosynthetic photon flux density (PPFD) was highest under red LED light, but only a third of the total PPFD under natural light. Seedlings grown under red light showed 60–100% more shoot dry weight and were 67–115% taller than seedlings grown in the greenhouse. However, seedlings under blue or white light conditions showed 67–76% less in biomass compared to greenhouse-grown seedlings. Overall, plant response of seedlings under red light condition was much better compared to greenhouse-grown seedlings emphasizing the importance of red light spectral quality in plant growth and development.